THE INTERPRETATION OF LOVE, MORAL AND ENLIGHTENED IDEAS IN SAYIDAHMAD VASLIY SAMARKANDIY`S WORK - Muxitdinova Badia Muslihiddinovna (Western European Studies, 2024)
In this article, the feature of Sayidahmad Vasliy Samarkandiy`s works, the scientific and enlightenment value of his divans, namely “Tuhfatul-ahbob” (the name his work) and Persian divan “Armogoni doston", are discribed. The poems of Vasliy`s creation, which were included in the divan, namely “Tuhfatul-ahbob”, comprising poems, praises, ghazals, muhammas, rubais, tarjebands and- muvashshahs (the type of gender) written over several years in different genres, were studied. In the Vasliy Samarkandiy also expressed about his ideas in his divan, on awakening the nation in the, reforming school education, studying science, promoting peace, self-awareness, and liberation from ignorance. The article analyses the poems of Vasily Samarkandiy on moral and educational topics, which are found in the Persian divan, namely “Armogoni doston”. It is noteworthy that the works that interested modern people in this divan and included the issues of socio-political, cultural, educational and daily life of that time and were characterized by a high degree of knowledge of aruz, cognitive rhyme, and knowledge of bade.
Keywords: divan; ideological and artistic features; romantic